Community preparedness for dam disaster and risk management - Muda, Rahsidi Sabri; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Md Amin, Mohamad Faiq; Norkhairi, Fatin Faiqa; Mohamad Nadzri, Amira Arisya (Otago Polytechnic, 2025)
This research investigates the critical components of community awareness and preparedness in relation to dam disaster and risk management. Dams, often regarded as remarkable engineering achievements, provide a wide range of benefits such as flood control, water supply, irrigation, hydropower generation, recreation, and navigation. Despite these advantages, the potential risks posed by dam failures or related disasters can result in severe social, economic, and environmental consequences, underscoring the urgent need for communities to be well-informed and prepared. This article reviews relevant scholarly and technical literature to examine key components of community awareness and preparedness in the context of dam disaster risk management. The review identifies recurring themes including the need for public education on dam risks, the effectiveness of communication systems, the role of emergency drills and simulations, and the integration of local knowledge into preparedness planning. The findings are aimed at identifying effective strategies to strengthen public knowledge of dam safety, reduce casualties, and mitigate losses during disaster events. By exploring the relationship between awareness and preparedness, the research offers valuable insights for policymakers, emergency responders, and local leaders in designing targeted programs that enhance resilience. The results highlight the necessity of sustained community education, regular dissemination of risk-related information, and the implementation of emergency drills and training sessions. Ultimately, the study advocates for continuous disaster-focused initiatives to foster self-reliant, resilient, and adaptive communities capable of withstanding dam-related hazards.